Country of birth affects blood pressure in the French hypertensive diabetic population - Aoun Bahous, Sola; Thomas, Frédérique; Pannier, Bruno; Danchin, Nicolas; SAFAR, MICHEL E. (Frontiers in Physiology, 2015)
Abstract: In large populations, individuals born in France have significantly different levels of blood pressure (BP) and cardiovascular (CV) risk factors than African and Asian populations born in their own country but living in France. Our objective was to investigate the impact of country of birth on BP and CV risk factors in a subpopulation selected on the basis of hypertension, either alone or associated with type 2 diabetes. In the individuals with hypertension alone, brachial systolic, diastolic, mean and pulse pressure (PP), heart rate, augmentation index and PP amplification were significantly higher in African-born than French- and Asian-born populations. In the individuals with hypertension and diabetes both, only augmentation index, PP amplification and brachial and central PP, but not brachial systolic, diastolic, mean BP and heart rate, were elevated when the African-born subgroup was compared to the French- and Asian-born populations. Increased body mass index and deprivation scores were consistently associated with the African-born population. The combination of diabetes and hypertension in African populations was associated with increased aortic stiffness and PP and greater body weight. In individuals with systolic hypertension, increased PP requires systolic BP to be reduced whereas notable reductions in diastolic BP may have deleterious consequences.